Experiences of being co-assistant: a pilot study - Irfani, Tri Hari; Gunawan, Joko; Tosepu, Ramadhan; Nuru, Hasanuddin (International Journal of Research in Medical Sciences, 2017)
Background: Co-assistant program is an important part in medical education in Indonesia. However, the evaluation for the effectiveness of this program is needed to produce the professional medical doctors. This study aimed to explore the experience of being co-assistance in medical education in Indonesia. Methods: This study used the descriptive qualitative approach by involving 12 medical doctors who had the experience of being co-assistant. The data in this study were analyzed by content analysis model using four cognitive processes: comprehending, synthesizing, theorizing, and re-contextualizing. Results: The findings emerged from the data consisted of having good learning experiences, seniority matter, and inappropriate examination. Conclusions: Considering the information from the students in this program was value, therefore, it is suggested that medical educators need to reconsider and evaluate the process of co-assistance program.